Exploration empirique de la richesse lexicale: la perception humaine - Bonvin, Audrey; Lambelet, Amelia (Linguistik Online, 2019)
We investigate how untrained readers perceive the lexical richness of short texts written by 8 to 10-year-olds in French, German and Portuguese. Seven untrained adults rated the lexical richness of a set of argumentative and narrative texts on Likert Scales while performing on a Think Aloud Protocol (TAP) task. Results show that raters consider other criteria than solely vocabulary in their assessments. Coherence, grammar and content seem to have a particular impact. Concerning vocabulary per se, (non-)repetition is mentioned regularly and other characteristics such as register, length of words, number of words appear as well. For this kind of texts, word frequency does not seem to be as salient as expected.